2010
DOI: 10.1074/jbc.m109.021246
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of Homocysteinylation of the Elastic Fiber Proteins Fibrillin-1 and Tropoelastin

Abstract: Homocystinuria caused by cystathionine-␤-synthase deficiency represents a severe form of homocysteinemias, which generally result in various degrees of elevated plasma homocysteine levels. Marfan syndrome is caused by mutations in fibrillin-1, which is one of the major constituents of connective tissue microfibrils. Despite the fundamentally different origins, both diseases share common clinical symptoms in the connective tissue such as long bone overgrowth, scoliosis, and ectopia lentis, whereas they differ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 58 publications
0
39
1
1
Order By: Relevance
“…Heparin is used as a cost-effective model of heparan sulfate as the two share a similar structure of repeating iduronic/glucuronic acid and N-sulfated glucosamine/N-acetylglucosamine disaccharide units. Heparin was cross-linked to BSA following a protocol established previously (32). Heparin-BSA protein concentrations were determined by BCA assay, and the pools were stored at Ϫ80°C until use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heparin is used as a cost-effective model of heparan sulfate as the two share a similar structure of repeating iduronic/glucuronic acid and N-sulfated glucosamine/N-acetylglucosamine disaccharide units. Heparin was cross-linked to BSA following a protocol established previously (32). Heparin-BSA protein concentrations were determined by BCA assay, and the pools were stored at Ϫ80°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the two glycosaminoglycans share a similar structure, and the clustering of heparan sulfate chains on cell surface proteoglycans is mimicked by coupling three to four heparin molecules per molecule of BSA. This established procedure has been used in many other studies (32,(35)(36)(37)(38).…”
Section: N-terminalmentioning
confidence: 99%
“…The sulfhydryl group of Hcy forms stable disulfide bonds with cysteine residues in proteins altering their structure and function [62]. Recently, Hubmacher et al demonstrated that homocysteinylation affected functional properties of fibrillin and tropoelastin [88]. Fibrillin and tropoelastin are essential components for the formation of elastic fibers.…”
Section: Roles Of H2s In Hcy-mediated Renovascular Pathophysiologymentioning
confidence: 99%
“…The N- and C-terminal regions of fibrillin colocalizes to form typical microfibril structure [90], and in this regard disulfide bond-mediated multimerization of the fibrillin-1 C-terminus and N- to C-terminal self-interaction are considered the initial steps for tissue microfibrils formation [91; 92]. Homocysteinylation reduces N- to –C-terminal fibrillin-1 self-interaction properties which is essential for biogenesis of microfibrils [88]. In addition, homocysteinylation on the disulfide bond in tropoelastin changes the self-assembly process which reduces elastic properties of blood vessels [88].…”
Section: Roles Of H2s In Hcy-mediated Renovascular Pathophysiologymentioning
confidence: 99%
“…NO is a powerful inhibitor of aggregation [13]. Various results indicate that Hcys or its thiolactone cause N-and S-homocysteinylation of human blood platelets, plasma proteins and other cellular or tissue proteins [14][15][16][17]. Moreover, both tested sulphurcontaining compounds reduce concentration of protein carbonyl groups.…”
Section: Introductionmentioning
confidence: 97%